Transparansi Timbangan dalam Jual Beli di Pasar Tradisional Inpres Kota Palu: Perspektif Keadilan dalam Muamalah - Nur Fadila; Taslia T; Nurhikma Febriana (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Traditional markets remain the primary source for meeting the daily needs of the people of Palu City, particularly for commodities sold by weight, such as vegetables, fish, meat, and other staple goods. This study aims to describe the practice of scale transparency among traders at the Inpres Traditional Market in Palu City and to analyze its conformity with the principle of justice in muamalah. A qualitative field-research approach was used, with data collected through observation, interviews with the market manager, four traders across different commodities, and two consumers, as well as documentation; data were analyzed through reduction, display, and verification, with validity maintained through source triangulation, method triangulation, and prolonged observation. The findings show that scale-transparency practices at Inpres Market are generally well implemented: scales are placed where buyers can see them, weighing is conducted openly, results are communicated directly, and traders are willing to re-weigh goods on request. However, some traders were still found to be unaware of the legal obligation to have their scales calibrated (tera), so that of the five transparency indicators analyzed, only the accuracy and fitness of the weighing instruments had not been fully achieved. Substantively, this practice already conforms to the principle of justice in muamalah — honesty (ash-shidq), openness, and l? ta?lim?na wa l? tu?lam?n (neither wronging nor being wronged) — thereby protecting consumers’ rights while still allowing traders a lawful margin of profit, although oversight and outreach on scale calibration by the relevant authorities still need to be strengthened.